Study of Basic Vegetation Composition in Sultan Thaha Saifuddin Grand Forest Park Area - Nursanti Nursanti; Ade Adriadi (Media Konservasi, 2019)
Research studies on the composition of basic vegetation in Sultan Thaha Saifuddin Grand  Forest Park area have been conducted from July to August 2018 with multiple plot vegetation method.. The plots placement was done by purposive sampling at two different land cover locations. The plot size sampling was 10x10 meters, 8 plots were located at the burnt location and 5 plots at the location of the bulian natural habitat. The results of the study found 37 families, and 80 species, where the family that has the highest number of species is the Moraceae family which is as many as 6 species. Plant species found in burned areas were 48 species, in non-burnt areas (bulian habitat) 29 species and in post-burned and non-burned area as many as 3 species. Keywords: basic vegetation, bulian habitat, burned areas, composition